2001
DOI: 10.1121/1.1334597
|View full text |Cite
|
Sign up to set email alerts
|

Distortion-product source unmixing: A test of the two-mechanism model for DPOAE generation

Abstract: This paper tests key predictions of the "two-mechanism model" for the generation of distortion-product otoacoustic emissions (DPOAEs). The two-mechanism model asserts that lower-sideband DPOAEs constitute a mixture of emissions arising not simply from two distinct cochlear locations (as is now well established) but, more importantly, by two fundamentally different mechanisms: nonlinear distortion induced by the traveling wave and linear coherent reflection off pre-existing micromechanical impedance perturbatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
204
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(211 citation statements)
references
References 41 publications
7
204
0
Order By: Relevance
“…Numerous studies support OHC electromechanics as the fundamental source of the emissions, because OAEs are reduced when OHCs are damaged or when the endocochlear potential, which is necessary for OHC electromotility is reduced (Henley et al 1996;Avan et al 2003;Mills 2003). For low primary levelevoked DPs, strong evidence has been shown that the generation of DPs can be summarized into a twosource model in which the generation sites are expected to be well localized to the f 2 and f dp places (Mauermann et al 1999a, b;Kalluri and Shera 2001). At moderate to high primary-tone levels, the cochlear excitation pattern broadens and regions responsible for the generation of OAEs appear to extend further basal (Martin et al 1999;Knight and Kemp 2001;Martin et al 2010).…”
Section: Propagation Of Dps In the Cochleamentioning
confidence: 99%
“…Numerous studies support OHC electromechanics as the fundamental source of the emissions, because OAEs are reduced when OHCs are damaged or when the endocochlear potential, which is necessary for OHC electromotility is reduced (Henley et al 1996;Avan et al 2003;Mills 2003). For low primary levelevoked DPs, strong evidence has been shown that the generation of DPs can be summarized into a twosource model in which the generation sites are expected to be well localized to the f 2 and f dp places (Mauermann et al 1999a, b;Kalluri and Shera 2001). At moderate to high primary-tone levels, the cochlear excitation pattern broadens and regions responsible for the generation of OAEs appear to extend further basal (Martin et al 1999;Knight and Kemp 2001;Martin et al 2010).…”
Section: Propagation Of Dps In the Cochleamentioning
confidence: 99%
“…The two backward waves sum to yield the DPOAE. The quasiperiodic, so-called fine structure of the DPOAE appears to derive from constructive and destructive interference between these backward waves (15). Recently, Boege and Janssen (19) showed that, under certain stimulus conditions, the cubic DPOAE can be used objectively to predict auditory threshold at f 2 .…”
mentioning
confidence: 99%
“…Although the underlying mechanisms remain largely unknown (e.g., refs. 11-13), there is strong evidence that DPOAEs, at least at low sound intensities, derive from two different regions along the cochlea (14), with a different mechanism being involved at each region (15)(16)(17)(18): the distortion-source emission and the reflection-source emission. The distortion-source emission appears to result from nonlinear interaction of the two primaries near and apical to the f 2 place, yielding the cubic distortion component of frequency 2f 1 Ϫ f 2 , which is directed both backward to the cochlear input and forward apically along the cochlea.…”
mentioning
confidence: 99%
“…In addition, the presence of the primary tones in the DPOAE paradigm suppresses amplification and/or reflection near the 2f 1 Àf 2 place, potentially modifying the results. Indeed, obtaining a close correspondence between the DPOAE R component and SFOAEs at the same frequency entails the use of an f 1 primary "mimicker" during the measurement of SFOAEs (Kalluri and Shera, 2001). Finally, possible biases introduced by the swept-tone analysis, including parameters such as the durations of the LSF and IFFT windows, remain to be systematically investigated.…”
Section: Discussionmentioning
confidence: 99%